Financial Flexibility, Cash holdings and liquidity: An Empirical Study - et. al., Arshad Abdul Amir Jassem Al- Shammari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to uncover the extent to which private commercial banks practice financial flexibility through their impact on cash liquidity and financial flexibility indicators (debt-equity ratio, cash flow, and public debt susceptibility) as an explanatory variable, and cash liquidity as a dependent variable and for its indicators (cash balance ratio, liquidity ratio) Legal, employment ratio (investment). In order to achieve the objectives of the study and answer the questions, the study was selected in the Iraqi private banking sector and the sample was applied to (10) banks using the data published on the website of the Iraq Stock Exchange. A detailed analysis (statistically and financially) of these two variables ((financial flexibility and cash liquidity)) was carried out in light of the data obtained for the study sample represented by the Iraq Stock Exchange for (10) from commercial banks affiliated with the Iraqi private sector according to specific inspection conditions, and for the period. (From 1/1/2019 to 12/31/2019), and by using many financial and statistical methods, the study concluded with a number of conclusions, perhaps the most important of which is the existence of a positive and moral correlation between indicators of financial flexibility and indicators of cash liquidity, as well as the existence of an impact relationship for indicators Financial flexibility on cash liquidity indicators, some of which are consistent with the study hypotheses, and some contradict them. The study came out with a number of recommendations, perhaps the most important of which is the necessity for bank administrations to characterize their financial plans for the issue of flexibility and its relevance to the formation of cash liquidity that would fulfill its obligations towards customers dealing with it and also work to face emergency conditions for it. Therefore, the banks ’reliance on financial flexibility indicators provides them with accurate insights about the optimal use of deposits that they can invest in in a way that generates cash assets for them.